Destination unknown : sustainable travel and ethical tourism - Lusby, Carolin (Common Ground Research Networks, 2021)
"Reflecting on the industry in a historical stand still offers a unique opportunity to rethink what is important in life. As the world has hit a universal reset button, we are allowed to imagine a travel and tourism that is fair, balanced, and resilient. Uncontrolled mass tourism and over- tourism have proven to have many negative impacts on societies, people, economies and environments. And while alternative forms of tourism have been shown to combat and mitigate some of these impacts, they are still niche markets. The tourism industry has the potential to take a leading role in fostering intercultural understandings, where local uniqueness and cultural diversity are both seen as assets, contributing to a memorable experience and excellent touristic product"--